HIV-1 controllers possess a unique CD8+ T cell activation phenotype and loss of control is associated with increased expression of exhaustion markers - Amber D. Jones; Zachary Capriotti; Erin Santos; Angel Lin; Rachel Van Duyne; Stephen Smith; Zachary Klase (PLoS ONE, 2025)
Background HIV-1 controllers are a rare population of individuals that exhibit spontaneous control of HIV-1 infection without antiretroviral therapy. Understanding the mechanisms by which HIV-1 controllers maintain and eventually lose this ability would be highly valuable in HIV-1 cure or vaccine research. Previous work revealed the ability of CD8 + T cells isolated from HIV-1 controllers to suppress HIV-1 replication in matched CD4 + T cells and PBMCs ex vivo and suggested the loss of control may be tied to CD8 + T cell exhaustion. Results We explored whether CD8 + T cell exhaustion plays a role in the maintenance and loss of control by examining immune characteristics of HIV-1 persistent controllers and transient controllers who lost control within the duration of the study. Using flow cytometry, we analyzed exhaustion marker expression on CD8 + T cells from HIV-1 controllers and determined that they maintain a unique exhaustion profile as compared to people without HIV-1 and HIV-1 standard progressors. The low level of T cell exhaustion seen in HIV-1 controllers was reversed when these individuals lost control and showed increased viral loads. Combinatorial immune checkpoint blockade targeting exhaustion markers was able to restore ex vivo control in CD8 + T cells from former controllers. Conclusions These results suggest that CD8 + T cell exhaustion compromises the ability to control viral replication in HIV-1 controllers. The character of exhaustion in response to HIV-1 and therapy is distinct in HIV-1 persistent controllers, transient controllers and standard progressors.